2021
DOI: 10.5194/bg-18-1375-2021
|View full text |Cite
|
Sign up to set email alerts
|

Intraseasonal variability of greenhouse gas emission factors from biomass burning in the Brazilian Cerrado

Abstract: Abstract. Landscape fires, often referred to as biomass burning (BB), emit substantial amounts of (greenhouse) gases and aerosols into the atmosphere each year. Frequently burning savannas, mostly in Africa, Australia, and South America are responsible for over 60 % of total BB carbon emissions. Compared to many other sources of emissions, fires have a strong seasonality. Previous research has identified the mitigation potential of prescribed fires in savanna ecosystems; by burning cured fuels early in the dry… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
27
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 23 publications
(34 citation statements)
references
References 80 publications
5
27
0
Order By: Relevance
“…It is not surprising that our values had a lower MCE and higher CH 4 EF than the biome means because we based our values on emissions from "wooded mesic sa-vannas" as opposed to the "grassland" values used in most savanna biome estimates. Wooded savannas contain small trees, shrubs and leaf litter, which tend to reduce MCE and increase methane EF values (e.g., Vernooij et al, 2021) due to the fraction of ligneous fuel in the mix.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is not surprising that our values had a lower MCE and higher CH 4 EF than the biome means because we based our values on emissions from "wooded mesic sa-vannas" as opposed to the "grassland" values used in most savanna biome estimates. Wooded savannas contain small trees, shrubs and leaf litter, which tend to reduce MCE and increase methane EF values (e.g., Vernooij et al, 2021) due to the fraction of ligneous fuel in the mix.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, there are not a lot of data in the literature on fine fuel mixtures (the primary fuel for savanna fires) used to estimate EFs in Africa, although the amount of woody vegetation clearly affects emissions (Korontzi, 2005;van Leeuwen and van der Werf, 2011). In the Brazilian Cerrado, for example, Vernooij et al (2021) found that the seasonal effect on methane EF was stronger in more woody savanna vegetation, with late dry season (LDS) fires having 20 % lower EF than early dry season (EDS) ones in shrub-dominated areas.…”
Section: Introductionmentioning
confidence: 99%
“…During the field experiments we filled single-polypropylene fitted Tedlar bags (SKC, type 232-01) with fresh smoke using a UAS-based (DJI, Matrice 200) sampling system. The UAS sampling methodology was described in detail in Vernooij et al (2021). In short, we filled 1L Tedlar bags with fresh smoke at altitudes of roughly 15 meters over the fire.…”
Section: Gas Sampling and Analysismentioning
confidence: 99%
“…Aircraft measurements maybe biased towards flaming emissions, since they sample lofted emissions that typically result from higher intensity combustion, (airplane), where as ground or tower based measuremetns maybe biased towards residual smouldering combustion (RSC) sampling since the smoke from higher intensity burns is lofted out of reach. Unmanned Aerial Systems (UAS) have the potential to offer a low-cost and versatile solution for sampling different locations within a freshly emitted, dense smoke plume (Aurell et al, 2021;Vernooij et al, 2021). UAS-compatible (i.e.…”
Section: Introductionmentioning
confidence: 99%